COVID-19 vaccine hesitancy: A telephonic survey in patients with systemic lupus erythematosusxs - Reuben Praharsh Kumar; Sandra Manuel; D Elizabeth; Vineeta Shobha (Indian Journal of Rheumatology)
Background: Vaccine against COVID-19 is an effective preventive measure; however, systemic lupus erythematosus (SLE) patients were excluded from the vaccine trials, which leads to questions regarding vaccine safety and efficacy, giving rise to vaccine hesitancy. We aim to study the prevalence of vaccine hesitancy among SLE patients and study the factors affecting it. Methods: The study is a cross-sectional telephone-based survey done on SLE patients. The questionnaire included a series of 15 questions pertaining to their baseline characteristics, COVID-19 infection and vaccination details, and their perceptions regarding the COVID-19 vaccine. Nonvaccinated individuals were defined as “willing” and “hesitant” based on their intent to get vaccinated. Results: Among 418 (93% women) participants, about 8% had contracted COVID-19 infection in the past. Nearly half had been vaccinated against COVID-19, and 83% had experienced one or more side effects which were largely mild. Out of the 215 nonvaccinated participants, 84% were “willing” and 16% were “hesitant.” Among the reasons for hesitancy, hasty vaccine production, fear of SLE flares, general vaccine refusal and limited transport facilities were significant. On the whole, 65.1% had a positive attitude toward the vaccine. Conclusion: Despite a low-hesitancy rate, the number of SLE patients with a negative attitude toward the COVID-19 vaccine is reasonably high, with more than half of the patients yet to be vaccinated. This highlights that the mistrust and negative perceptions of the vaccine still persists. The role of health-care providers in vaccine acceptance in SLE patients is crucial.